2023
DOI: 10.1097/md.0000000000036441
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of whole-body vibration in patients with cerebral palsy: A systematic review and meta-analysis

Yong-Gu Han,
Myoung-Kwon Kim

Abstract: Background: This study examined the effects of systemic vibration exercises on cerebral palsy patients. Methods: Literature published in Cumulated Index to Nursing and Allied Health Literature (CINAHL), Cochrane library, Embase, Physiotherapy Evidence Database (PEDro), and PubMed was reviewed. A total of 2978 studies were initially retrieved. After further reading of the full texts 17 articles were finally included. A quality assessment of the included … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 54 publications
0
1
0
Order By: Relevance
“…Analyzing the relationships between the control parameters and key biomechanical indicators and achieving standardized comparisons between different control strategies may better guide the future technological development of exoskeleton robot-assisted walking rehabilitation. Recent clinical trials have also revealed that treatment methods developed in neurorehabilitation have been widely studied in CP research, such as transcranial magnetic stimulation ( 48 ), virtual reality technology ( 48 ), whole-body vibration ( 49 ), wearable exoskeletons, and stem cell transplantation ( 45 , 50 52 ).…”
Section: Discussionmentioning
confidence: 99%
“…Analyzing the relationships between the control parameters and key biomechanical indicators and achieving standardized comparisons between different control strategies may better guide the future technological development of exoskeleton robot-assisted walking rehabilitation. Recent clinical trials have also revealed that treatment methods developed in neurorehabilitation have been widely studied in CP research, such as transcranial magnetic stimulation ( 48 ), virtual reality technology ( 48 ), whole-body vibration ( 49 ), wearable exoskeletons, and stem cell transplantation ( 45 , 50 52 ).…”
Section: Discussionmentioning
confidence: 99%